Expressão protéica SOX2, SOX3, SOX10 e sua relação com aspectos histológicos e proliferativos em melanomas caninos orais - Renato Felipe da Costa (2021)
The aggressiveness of oral melanoma can be related to several mutations that occur during development, both in humans and in the canine species. Among the different changes in protein expression observed in this neoplastic type, the change in proteins of the SOX family is described. In this work, the expression of SOX2, SOX3, and SOX10 and its relationship with the proliferative index and histological aspects indicative of aggressiveness in canine oral melanomas were evaluated. Thirty canine oral melanomas were histologically reviewed and the expression of Melan-A, SOX2, SOX3, SOX10, and Ki67 in these tumors were determined. All tumors presented histomorphological characteristics compatible with malignant tumors and immunopositivity for Melan-A, confirming the diagnosis of malignant oral melanocytic neoplasia. The expression of SOX2, SOX3, and SOX10 was observed in 7/30 (23.33%), 20% (6/30), and 23/30 (76.67%) of the cases, respectively. Among the analyzed markers, the relationship between the higher expression of SOX3 in tumors with lower proliferative indexes was highlighted. An inverse correlation was also observed between the expression cytoplasmic SOX10 and nuclear SOX10, suggesting a change in the location of this protein in oral melanomas. Apparently, among the SOX family proteins studied, the SOX3 protein plays an important role in the regulation of cell proliferation in oral melanomas, and it is suggested that the SOX2 and SOX10 proteins are constitutively expressed in these neoplasms, without a determining role for aggressiveness. New studies of this gene transcription pathway may assist in possible prognostic and predictive determinations of the SOX3 protein in oral canine melanoma.